Seasonal occurrence, distribution and group size of Irrawaddy dolphins (Orcaella brevirostris) in the bay of Brunei, Brunei Darussalam - Farah Dayana Haji Ismail; Nurlisa Azizul; Saifullah Arifin Jaaman; Azmi Marzuki Muda; Mohd Vol Momin; Bohari Abdullah; Zhang, Xuelei; Hairul Masrini Muhamad (Penerbit Universiti Kebangsaan Malaysia, 2021)
The uniqueness of the Bay of Brunei makes it an ideal place to be inhabited by Irrawaddy dolphins. However, the increasing potential impacts of anthropogenic factors and environmental changes on the dolphins are alarming. The objectives of this study were to determine the seasonal occurrence and distribution, and to estimate the group size of Irrawaddy dolphins in the Bay of Brunei. Surveys were conducted between January 2016 and April 2018. The total distance surveyed was 2,439.2 km in 189.13 h (survey effort = 13,081.93 km.h). Forty-nine groups of Irrawaddy dolphins were recorded with a sighting rate of 0.37 per 100 km.h. Thirteen of the groups were observed with calves. Overall, the group size ranged between 1 and 15 individuals with a mean of 4.5 individuals (SD = 3.3). There was no statistical significance in the number of dolphin sightings between four different monsoon seasons (Northeast, Southwest, April Inter-monsoon, and October Inter-monsoon) (χ2 = 5.66, df = 3, p > 0.05). The number of sightings and number of individuals suggest that Irrawaddy dolphins are residents of the Bay of Brunei and are in need of a conservation management plan.